Association between the TIMD4-HAVCR1 variants and serum lipid levels, coronary heart disease and ischemic stroke risk and atorvastatin lipid-lowering efficacy. Issue 1 (19th January 2018) - Zhang, Qing-Hui; Yin, Rui-Xing; Chen, Wu-Xian; Cao, Xiao-Li; Chen, Yu-Ming
Abstract : Little is known about the association of the TIMD4 (T-cell immunoglobulin and mucin domain 4 gene)- HAVCR1 (hepatitis A virus cellular receptor 1) variants and lipid metabolism, the risk of coronary heart disease (CHD) and ischemic stroke (IS). The present study aimed to determine the TIMD4-HAVCR1 variants, their haplotypes and gene–environment interactions on serum lipid levels, the risk of CHD and IS, and the lipid-lowering efficacy of atorvastatin in a southern Chinese Han population. Genotypes of three variants in 622 controls, 579 CHD, and 546 IS patients were determined by the Snapshot technology. Atorvastatin calcium tablet (20 mg/day) was given in 724 hyperlipidemic patients for 8 weeks after genotyping. The rs12522248 genotypic and allelic frequencies were different between controls and patients, and were associated with the risk of CHD and IS. The rs1501908G-rs12522248T-rs2036402T haplotype was associated with an increased risk of CHD; the G-C-T haplotype was associated with lower risk of CHD; and the C-C-C haplotype was associated with an increased risk of IS. Variants and their haplotypes in controls were associated with triglyceride (rs1501908), low-density lipoprotein cholesterol (LDL-C, rs1501908, G-T-T), high-density lipoprotein cholesterol (HDL-C, rs12522248, C-C-C) and the ratio of total cholesterol (TC) to HDL-C (C-C-C). Interactions of rs1501908- and rs2036402-alcohol (HDL-C); rs1501908- and rs12522248-high body mass index (hBMI, ≥24 kg/m 2 ; TC); and TIMD4-HAVCR1 variants-atorvastatin on several lipid parameters were detected. Interactions of rs12522248TC/CC-hBMI, G-T-T-, and C-C-C-smoking on the risk of CHD; and C-C-C-smoking, C-C-C-, and G-C-T-hBMI on the risk of IS were also observed. These findings suggest that the TIMD4-HAVCR1 variants may be the genetic risk factors for CHD and IS.